Enhancing carotenoid production in Chlorella sorokiniana through the protein–protein interaction between ORANGE and PSY - Ruijuan Ma; Xi Li; Xing Meng; Zhen Zhang; Yucheng Chen; Chunxiao Zhang; Ling Wang; Kangle Lu; Xueshan Li; Kai Song; Shih-Hsin Ho; Jianfeng Chen; et al. (Bioresource Technology, 2026)

Habitat heterogeneity and hydrological seasonality jointly shape the taxonomic and functional diversity of aquatic insects in inland saline–alkaline wetlands of Northeast China - Jiaxing Shi; Kangle Lu; Lei Xu; Jiping Liu; Haitao Wu (Hydrobiologia, 2026)

Comparative Analysis of Immune Function and Intestinal Health of Lateolabrax maculatus Fed with Defatted Tenebrio molitor Larvae Meal Diet and Showing Different Growth Rates - Jin Huang; Kefu Liu; Ling Wang; Xueshan Li; Kai Song; Ruijuan Ma; Kangle Lu; Kequan Chen; Guijuan Yu; Chunxiao Zhang (Journal of Ocean University of China, 2026)

25-hydroxyvitamin D3 enhances growth and immunity in Litopenaeus vannamei by modulating gut health and hepatopancreatic gene expression: A comparative study with vitamin D3 - Guanda Zhu; Junbo Wang; Kangle Lu; Naifeng Li; Shudao Huang; Yingtiao Lai; Feifei Wang; Ling Wang; Chunxiao Zhang; Hua Gong (Aquaculture, 2026)

Effects of Agricultural Ditch Networks and Land Use on Dissolved Organic Matter Characteristics in Naoli River Basin, Sanjiang Plain, China - Haobo Wu; Zhongsheng Zhang; Wenwen Zhao; Jiaxing Shi; Luan Sang; Haitao Wu; Kangle Lu; Qiang Guan (Chinese Geographical Science, 2026)

Nocturnal water balance shifts: Uncovering the forces driving transpiration and refilling in a montane forest - Hongjuan Zhou; Lu Han; Kangle Mo; Guodong Jia; Lixin Chen; Zhiqiang Zhang (Agricultural and Forest Meteorology, 2026)

Increasing Elevation Reduces Complexity of Soil Microbial Co-occurring Network in Changbai Mountains, China - Xue Liu; Haitao Wu; Qiang Guan; Kangle Lu; Dandan Liu; Yujuan Kang; Shixiu Zhang (Chinese Geographical Science, 2026)

Establishment and characterization of muscle cell line of spotted seabass (Lateolabrax maculatus) - Xiaoli Zheng; Jibin Lin; Ling Wang; Kai Song; Kangle Lu; Xueshan Li; Chunxiao Zhang (Fish Physiology and Biochemistry, 2025)

Black soldier fly (Hermetia illucens Linnaeus) larvae meal - a promising protein source in bullfrog (Aquarana catesbeiana) feed - Lin Zhou; Kequan Chen; Kai Song; Kangle Lu; Xueshan Li; Ling Wang; Chunxiao Zhang (Aquaculture, 2025)

Predicting the potential geographical distribution of peatlands in Northeast China based on the ensemble model - Haobo Wu; Zhongsheng Zhang; Zhenshan Xue; Wenwen Zhao; Luan Sang; Haitao Wu; Wenfeng Wang; Qiang Guan; Kangle Lu (Global and Planetary Change, 2025)

Dietary tauroursodeoxycholic acid supports growth and gut health in spotted seabass (Lateolabrax maculatus) under thermal stress conditions - Yongping Liu; Xiaojiang Mao; Kai Song; Ling Wang; Xueshan Li; Chunxiao Zhang; Kangle Lu; Samad Rahimnejad (Fish & Shellfish Immunology, 2025)

Addition of phytase to a high plant protein-low phosphorus diet increases growth and nutrient absorption and alleviates intestinal damage in bullfrogs (Lithobates catesbeianus) - Fashun Su; Yuezhen Huang; Hongyong Hu; Ling Wang; Kai Song; Kangle Lu; Chunxiao Zhang; Xueshan Li (Animal Feed Science and Technology, 2025)

High temperature changes the structure and function of spotted seabass (Lateolabrax maculatus) tissues and causes ER stress and mitochondrial homeostasis imbalance in liver - Xin Yang; Ling Wang; Kangle Lu; Xueshan Li; Kai Song; Chunxiao Zhang (Aquaculture, 2025)

Nitrogen and phosphorus budgets of the bullfrog (Aquarana catesbeiana) in different body weights - Xinyuan Li; Nan Jin; Weiqiang Wu; Xueshan Li; Kangle Lu; Kai Song; Peng Li; Zexiong Chen; Mohamed Mohsen; Ling Wang; Chunxiao Zhang (Aquaculture, 2025)

Slow recovery in trophic structure of restored wetlands in Northeast China - Kangle Lu; Zhanyan Chen; Xinhua He; Haitao Wu; Fengzhi He (Science of The Total Environment, 2024)

High temperature induces oxidative stress in spotted seabass (Lateolabrax maculatus) and leads to inflammation and apoptosis - Xin Yang; Ling Wang; Kangle Lu; Xueshan Li; Kai Song; Chunxiao Zhang (Fish & Shellfish Immunology, 2024)

Dietary phosphorus requirement of bullfrog Aquarana catesbeiana - Fashun Su; Ling Wang; Kai Song; Kangle Lu; Xueshan Li; Chunxiao Zhang (Aquaculture, 2024)

Microplastic Contamination in Aquafeed Ingredients Used as Protein and Carbohydrate Sources - Mohamed Mohsen; Fashun Su; Jibin Lin; Xueshan Li; Kangle Lu; Chunxiao Zhang (Bulletin of Environmental Contamination and Toxicology, 2024)

Ant mound constructions reduce chemical diversity but increase network complexity of soil organic matter: A case from drained peatlands in Northeast China - Wenwen Zhao; Xuehui Zhang; Zhongsheng Zhang; Qiang Guan; Kangle Lu; Wenfeng Wang; Haitao Wu (Applied Soil Ecology, 2024)

Heat stress-induced dysbiosis of the gut microbiota impairs spermatogenesis by regulating secondary bile acid metabolism in the gut - Guitian He; Boqi Zhang; Kangle Yi; Tong Chen; Caomeihui Shen; Maosheng Cao; Nan Wang; Jinxin Zong; Yueying Wang; Kening Liu; Fuqiang Chang; Xue Chen; et al. (Science of The Total Environment, 2024)

Food web restoration lags behind biological communities: a case study from a floodplain wetland - Lei Xu; Qiang Guan; Kangle Lu; Jiamin Liu; Xiaoyang Ming; Manhong Liu; Haitao Wu (Hydrobiologia, 2024)

Photocatalytic degradation of sulfonamides in suspensions of coral-like graphene carbon nitride with nitrogen vacancies - Laiyan Wu; Zi Lu; Jingyao Liao; Xiaofan Xiang; Hongyan Song; Anping Yang; Zafar Hussain Ibupoto; Kangle Lv (Chemosphere, 2024)

Low phosphorus increases hepatic lipid deposition, oxidative stress and inflammatory response via Acetyl-CoA carboxylase-dependent manner in zebrafish liver cells - Jibin Lin; Jilei Zhang; Weiwei Dai; Xiao Li; Mohamed Mohsen; Xueshan Li; Kangle Lu; Kai Song; Ling Wang; Chunxiao Zhang (Fish & Shellfish Immunology, 2024)

The effects of microbiota on reproductive health: A review - Nan Wang; Lu Chen; Kangle Yi; Baizhong Zhang; Chunjin Li; Xu Zhou (Critical Reviews in Food Science and Nutrition, 2024)

Optimal dietary protein level for the growth and metamorphosis of bullfrog (Lithobates catesbeianus) tadpoles - Juan Gao; Xueshan Li; Kangle Lu; Kai Song; Jian Zhang; Ling Wang; Chunxiao Zhang (Aquaculture, 2024)

The impacts of reduced connectivity on multiple facets of aquatic insect diversity in floodplain wetlands, Northeast China - Kangle Lu; Haitao Wu; Sonja C. Jähnig; Fengzhi He (Science of The Total Environment, 2024)

Construction of oxidation-reduction bifunctional nano-purifiers: S-scheme faceted heterojunction BiOCl(110) nanosheets/TiO2(001) hollow nanocubes with abundant oxygen vacancies for balancing visible photocatalytic activity - Yanfei Lu; Lianqing Chen; Chengjiang Zhang; Mengxue Yu; Kangle Lv; Xianghong Li; Benjun Xi (Journal of Environmental Chemical Engineering, 2024)

High water temperature raised the requirements of methionine for spotted seabass (Lateolabrax maculatus) - Xin Yang; Qinjiang Weng; Xueshan Li; Kangle Lu; Ling Wang; Kai Song; Chunxiao Zhang; Samad Rahimnejad (Fish Physiology and Biochemistry, 2024)

Na2S-modified biochar for Hg(II) removal from wastewater: A techno-economic assessment - Wenwen Zhao; Zhongsheng Zhang; Yuan Xin; Ran Xiao; Feng Gao; Haitao Wu; Wenfeng Wang; Qiang Guan; Kangle Lu (Fuel, 2024)

Effects of dietary zinc levels on growth, intestinal health, antioxidant and non-specific immunity of spotted seabass (Lateolabrax maculatus) reared at two temperatures - Jun Yuan; Xiao Li; Kai Song; Xueshan Li; Chunxiao Zhang; Kangle Lu; Ling Wang (Aquaculture, 2023)

Enhanced intestinal microflora composition and phosphorus-transportation efficiency in fast-growing spotted seabass (Lateolabrax maculatus) fed a low-phosphorus diet - Jiarong Guo; Jibin Lin; Xueshan Li; Ling Wang; Kai Song; Kangle Lu; Chunxiao Zhang (Aquaculture, 2023)

Methanotroph (Methylococcus capsulatus, Bath) bacteria meal alleviates soybean meal-induced enteritis in spotted seabass (Lateolabrax maculatus) by modulating immune responses and the intestinal flora - Jian Zhang; Manhan Yu; Jia Wang; Matt Longshaw; Kai Song; Ling Wang; Xueshan Li; Chunxiao Zhang; Kangle Lu (Aquaculture, 2023)

Combination of mineral protection and molecular characteristics rather than alone to govern soil organic carbon stability in Qinghai-Tibetan plateau wetlands - Wenwen Zhao; Zhongsheng Zhang; Xuehui Zhang; Lei Xu; Qiang Guan; Kangle Lu; Haitao Wu; Wenfeng Wang (Journal of Environmental Management, 2023)

Responses of riparian insect communities to flow regulation in riverine wetlands of Northeastern China - Yao Meng; Haitao Wu; Qiang Guan; Kangle Lu; Yujuan Kang; Guanhua Dai (Hydrobiologia, 2023)

Postbiotics of Bacillus subtilis LCBS1 have beneficial effects on bullfrogs (Lithobates catesbeianus) - Bingyi Tao; Chunxiao Zhang; Xiao Li; Xueshan Li; Kangle Lu; Kai Song; Ling Wang (Aquaculture, 2023)

Microplastics cause reproductive toxicity in male mice through inducing apoptosis of spermatogenic cells via p53 signaling - Chunsheng Lu; Yuehui Liang; Ya Cheng; Chan Peng; Yuanyuan Sun; Kangle Liu; Yingqing Li; Yixia Lou; Xiao Jiang; Aihua Zhang; Jinyi Liu; Jia Cao; et al. (Food and Chemical Toxicology, 2023)

Effects of dietary vitamin E levels on growth, antioxidant capacity and immune response of spotted seabass (Lateolabrax maculatus) reared at different water temperatures - Xueshan Li; Jingcheng Sun; Ling Wang; Kai Song; Kangle Lu; Lu Zhang; Xuekun Ma; Chunxiao Zhang (Aquaculture, 2023)

Effects of dietary creatine levels on the growth, muscle energy metabolism and meat quality of spotted seabass (Lateolabrax maculatus) fed low-fishmeal diets - Jibin Lin; Yanqin Liao; Xueshan Li; Kangle Lu; Kai Song; Ling Wang; Lu Zhang; Chunxiao Zhang (Aquaculture, 2023)

Effects of dietary iron levels on growth performance, iron metabolism and antioxidant status in spotted seabass (Lateolabrax maculatus) reared at two temperatures - Zhe Wang; Xueshan Li; Kangle Lu; Ling Wang; Xuekun Ma; Kai Song; Chunxiao Zhang (Aquaculture, 2023)

Substituting Fish Meal with a Bacteria Protein (Clostridium autoethanogenum Protein) Derived from Industrial-Scale Gas Fermentation: Effects on Growth and Gut Health of Juvenile Large Yellow Croakers (Larimichthys crocea) - Jian Zhang; Yanzou Dong; Kai Song; Ling Wang; Xueshan Li; Kangle Lu; Beiping Tan; Chunxiao Zhang (Fishes, 2022)
This study was conducted to investigate the effects of Clostridiumautoethanogenum protein (CAP) replacement for fish meal (FM) on growth performance, digestive enzyme activity, humoral immunity and liver and intestinal health in large yellow croakers (Larimichthys crocea). Four experimental diets were formulated by replacing FM with CAP at different levels—0% (CAP0), 15% (CAP15), 30% (CAP30) and 45% (CAP45). Triplicate groups of juveniles (initial weight = 11.86 ± 0.13 g) were fed the test diets to apparent satiation two times daily for eight weeks. There was no significant difference in final body weight (FBW), weight gain rate (WG) and feed efficiency (FE) between CAP0 and CAP15. However, compared to the CAP0, CAP30 and CAP45 significantly reduced FBW, WG and LDR (p 0.05). Compared to CAP0, CAP30 and CAP45 significantly reduced serum C4 concentration (p

Hydroxytyrosol Attenuates High-Fat-Diet-Induced Oxidative Stress, Apoptosis and Inflammation of Blunt Snout Bream (Megalobrama amblycephala) through Its Regulation of Mitochondrial Homeostasis - Yanzou Dong; Tian Xia; Manhan Yu; Ling Wang; Kai Song; Chunxiao Zhang; Kangle Lu (Fishes, 2022)
The present study was conducted to investigate the effects of dietary hydroxytyrosol (HT) on oxidative stress, inflammation and mitochondrial homeostasis in blunt snout bream (Megalobrama amblycephala). Fish were fed a low-fat diet (LFD, 5% lipid), a high-fat diet (HFD, 15% lipid), an LFD supplementing 200 mg/kg HT, or an HFD supplementing 200 mg/kg HT. After 10-week feeding, significant reduction of growth was observed in fish fed HFD, compared with other groups. HFD caused oxidative stress and more apoptosis of hepatocytes, while HT addition resulted in significant decrease of ROS and MDA contents, and the apoptotic hepatocytes. Moreover, the expression of genes involving inflammation of HFD group were elevated. Supplementing HT to HFD can attenuate this. All the activities of complexes of mitochondria in the HFD group were decreased compared with those in the LFD group, while supplementing HT to HFD significantly increased complex I-III activities. Furthermore, HFD downregulated the expressions of Atg5 and NRF-1 which induced the failure of mitophagy and biogenesis, while, supplementing HT to HFD reversed these expressions involving mitochondrial autophagy and biogenesis. In summary, adding HT to HFD relieved oxidative stress, apoptosis and inflammation, likely due to its regulation of mitochondrial homeostasis.

Aquatic invertebrate assemblages during the spring-thaw season in wetlands of Northeastern China - Kangle Lu; Darold P. Batzer; Haitao Wu (Hydrobiologia, 2021)

Effects of Ecological Restoration on Trophic Dynamics in Estuarine Wetlands - Haitao T. Wu; Mengyao Y. Yang; Kangle L. Lu; Darold P. Batzer (Wetlands, 2021)

Molecular cloning, expression HSP70 and its response to bacterial challenge and heat stress in Microptenus salmoides - Chunnuan Zhang; Kangle Lu; Junhui Wang; Qi qian; Xiaoyu Yuan; Changchang Pu (Fish Physiology and Biochemistry, 2020)

Effects of Hydrological Connectivity on Snail Assemblages in the Intertidal Zone of Coastal Wetlands - Haitao Wu; Qiang Guan; Kangle Lu; Guangxuan Han; Baoquan Li; Mengyao Yang (Wetlands, 2020)

A Macroinvertebrate Multimetric Index for the Bioassessment of Wetlands Adjacent to Agriculture Fields in the Sanjiang Plain, China - Haitao Wu; Kangle Lu; Xianguo Lyu; Zhenshan Xue (Chinese Geographical Science, 2019)

Aquatic macroinvertebrate assemblages in wetlands of Northeastern China - Haitao Wu; Qiang Guan; Kangle Lu; Darold P. Batzer (Hydrobiologia, 2019)

Effects of berberine on growth, liver histology, and expression of lipid-related genes in blunt snout bream (Megalobrama amblycephala) fed high-fat diets - Wenhao Zhou; Samad Rahimnejad; Kangle Lu; Lina Wang; Wenbin Liu (Fish Physiology and Biochemistry, 2019)

Development of a multi-metric index based on aquatic invertebrates to assess floodplain wetland condition - Kangle Lu; Haitao Wu; Zhenshan Xue; Xianguo Lu; Darold P. Batzer (Hydrobiologia, 2019)

Longitudinal and lateral variation in snail assemblages along a floodplain continuum - Qiang Guan; Haitao Wu; Kangle Lu; Xianguo Lu; Darold P. Batzer (Hydrobiologia, 2017)

Effect of trichlorfon on oxidative stress and hepatocyte apoptosis of Carassius auratus gibelio in vivo - WeiNa Xu; WenBin Liu; KangLe Lu; YangYang Jiang; GuiFeng Li (Fish Physiology and Biochemistry, 2012)

Patterns of variation of the major histocompatibility complex class IIB loci in Chinese goose (Anser Cygnoides) - Xu Zhou; Chunjin Li; Kangle Yi; Hongyan Liang; Lu Chen; Yanling Sun; Shuling Niu; Wei Wu (Immunogenetics, 2009)